SOSIOLOGI SIMBOLIK TARIAN LALAYON: RELASI BUDAYA, IDENTITAS, DAN STRUKTUR SOSIAL DI WEDA MALUKU UTARA - Alhaddad, Yahya (JSPH : Jurnal Sosial Politik Humaniora, 2025)
The Lalayon dance is a form of cultural expression of the Vedic people of North Maluku, rich in symbolic meaning. This study aims to understand how the Lalayon dance shapes and represents social identity and reflects cultural relations and the social structure of the Vedic people. The method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results show that the Lalayon dance functions not only as entertainment but also as a medium for conveying cultural values, a symbol of community identity, and a means of reproducing social structure. The Lalayon dance is not merely a means of entertainment but also contains deep meaning that reflects the value system, norms, and social structure of the Vedic people. Furthermore, Lalayon serves as a vehicle for transmitting ancestral values to the younger generation, strengthening social solidarity, and clarifying existing social stratification. Thus, this research contributes to the development of cultural sociology studies, particularly regarding symbolism in traditional performing arts.